Facilitators to doctoral completion among international students in a Global South University: An appreciative inquiry perspective - Songcun Zhang; Hui Zhan (PLoS ONE, 2026)
In the context of the global knowledge economy, the Global South has emerged as an increasingly important destination for doctoral education, yet research on this phenomenon remains scarce. The present study addresses this research gap by investigating the factors that contribute to the successful completion of doctoral programs among international students from the Global South enrolled at a public research university in Malaysia. Employing the Appreciative Inquiry approach, this study conducted semi-structured interviews with 11 international doctoral graduates. Findings reveal that intrinsic factors, such as passion for research, perseverance, and self-discipline, are crucial for success. External factors, including support from supervisors, institutions, families, and friends, also play a significant role. Furthermore, the Global South participants in this study called for improving conditions for future cohorts and fostering cross-cultural understanding within South-South doctoral education, where resource constraints and uneven institutional support often necessitate mutual aid and solidarity, a dimension largely overlooked in studies focused on Global Northern higher education systems with more robust infrastructure. The study contributes to understanding doctoral experiences in the Global South, challenges the dominance of a northern-centric perspective in academic research, and offers practical implications for institutions seeking to enhance support for doctoral students.